Controllable Growth of High‐Quality Inorganic Perovskite Microplate Arrays for Functional Optoelectronics. Issue 17 (12th March 2020) - Gu, Zhenkun; Zhou, Zhonghao; Huang, Zhandong; Wang, Kang; Cai, Zheren; Hu, Xiaotian; Li, Lihong; Li, Mingzhu; Zhao, Yong Sheng; Song, Yanlin
Abstract: Inorganic perovskite single crystals have emerged as promising vapor‐phase processable structures for optoelectronic devices. However, because of material lattice mismatch and uncontrolled nucleation, vapor‐phase methods have been restricted to random distribution of single crystals that are difficult to perform for integrated device arrays. Herein, an effective strategy to control the vapor‐phase growth of high‐quality cesium lead bromide perovskite (CsPbBr3 ) microplate arrays with uniform morphology as well as controlled location and size is reported. By introducing perovskite seeds on substrates, intractable lattice mismatches and random nucleation barriers are surpassed, and the epitaxial growth of perovskite crystals is accurately controlled. It is further demonstrated that CsPbBr3 microplate arrays can be monolithically integrated on substrates for the fabrication of high‐performance lasers and photodetectors. This strategy provides a facile approach to fabricate high‐quality CsPbBr3 microplates with controllable size and location, which offers new opportunities for the scalable production of integrated optoelectronic devices. Abstract : A facile strategy for a vapor‐phase patterning inorganic perovskite single crystal array is demonstrated to fabricate high‐performance micro‐optoelectronic devices. This strategy allows growth of high‐quality inorganic perovskite single crystals with controllable size and location. It provides new opportunities to explore the inorganic perovskite single‐crystal array for various integrated optoelectronics applications.